Promotion Management Strategy in Improving the Quality of Education at SDIT 'Al Imaroh Cikarang Barat-Bekasi - Diansah, Roy; Hermanto; Apriliantoni (Faculty of Tarbiyah, Institut Agama Islam Negeri (IAIN) Kediri, Indonesia, 2023)
Al'Imaroh Integrated Islamic Elementary School (SDIT Al’Imaroh) has a new product that must be offered to the community, SDIT Al’Imaroh Cikrang Barat Bekasi is in great demand by the community, the number of students registering is increasing, exceeding its capacity. This is an interesting factor to study, what is the marketing strategy. One of the effective marketing methods is the kinship model. In fact, many parents of new students end up getting to know and are interested in the institution because they get references from friends, relatives or co-workers in the office. This qualitative research obtains data from what is known, done, experienced and felt by informants. A school environment that is healthy and beautiful then with a school program that supports the curriculum by memorizing the Qur'an, memorizing daily prayers is a new product for the community. Services for basic educational needs are highly prioritized, for example exemption or relief from school fees, scholarships for outstanding children, health checks and child development consultations.